The Influence of Intellectual Capital on Financial Performance: Environmental, Social, Governance (ESG) Moderation (Study of Companies Listed on the Indonesian Stock Exchange) - Febrianti, Rosa Ade; Rahmayanti, Dewi (PT FORMOSA CENDEKIA GLOBAL, 2023)
Intellectual Capital or intangible assets are very important for company sustainability. This research aims to assess how intellectual capital influences the financial performance of 36 companies listed on the Indonesia Stock Exchange (BEI), which have implemented ESG practices from 2017 to 2021. Intellectual capital is measured by utilizing the VAICTM model developed by Pulic, as well as evaluating the moderating influence of ESG on the relationship between intellectual capital and financial performance. The approach applied in this research is a quantitative method, which involves steps such as classical assumption testing, multiple regression analysis, and moderation regression testing. The findings from the research conclude that the two components of intellectual capital have a positive and significant influence on the financial performance of companies in Indonesia.